Hypothesis: The Vestibular and Cerebellar Basis of the Mal de Debarquement Syndrome - Cohen, Bernard; Yakushin, Sergei B.; Cho, Catherine (Frontiers in Neurology, 2018)
The Mal de Debarquement Syndrome (MdDS) generally follows sea voyages, but it can occur after turbulent flights or spontaneously. The primary features are objective or perceived continuous rocking, swaying, and/or bobbing at 0.2 Hz after sea voyages or 0.3 Hz after flights. The oscillations can continue for months or years and are immensely disturbing. Associated symptoms appear to be secondary to the incessant sensation of movement. We previously suggested that the illness can be attributed to maladaptation of the velocity storage integrator in the vestibular system, but the actual neural mechanisms driving the MdDS are unknown. Here, based on experiments in subhuman primates, we propose a series of postulates through which the MdDS is generated: 1. The MdDS is produced in the Velocity Storage integrator by activation of Vestibular Only (VO) neurons on either side of the brainstem that are oscillating back and forth at 0.2 or 0.3 Hz. 2. The groups of VO neurons are driven by signals that originate in Purkinje cells in the cerebellar nodulus. 3. Prolonged exposure to roll, either on the sea or in the air, conditions the roll-related neurons in the nodulus. 4. The prolonged exposure causes a shift of the pitch orientation vector from its original position aligned with gravity to a position tilted in roll. 5. Successful treatment involves exposure to a full-field optokinetic stimulus rotating around the spatial vertical countering the direction of the vestibular imbalance. This is done while rolling the head at the frequency of the perceived rocking, swaying or bobbing. We also note experiments that could be used to verify these postulates, as well as considering potential flaws in the logic. Important unanswered questions: 1. Why does the MdDS predominantly affect women? 2. What aspect of roll causes the prolongation of the tilted orientation vector, and why is it so prolonged in some individuals? 3. What produces the increase in symptoms of some patients when returning home, and how can this be avoided? We also posit that the same mechanisms underlie the less troublesome and shorter duration Mal de Debarquement.